PENGARUH KUALITAS AUDIT TERHADAP KUALITAS PELAPORAN KEUANGAN PADA INSPEKTORAT KOTA SUKABUMI: accounting & finance - Asep Suryana, SE., M.AK (Ekonomedia, 2019)
The purpose of this research is to know how much audit quality affects the quality of financial reporting in Inspektorat Kota Sukabumi.The method used for this study is a qualitative method, which has a descriptive nature and tends to use analysis. In terms of the size of respondents or research objects, qualitative methods have fewer objects compared to quantitative research, because they prioritize the depth of data, not the quantity of data.The results of the study that the variable X namely Audit Quality in Inspektorat Kota Sukabumi is classified as good and can be seen from the assessments that have been carried out showing the correlation of Audit Quality (X) to the Quality of Financial Reporting of r = 0.620, which means it is in the range of 0.60-0.79 which means strong, then when there is an increase in the audit quality variable, the variable quality of financial reporting will increase and vice versa.